Developing a self-healing supramolecular nucleoside hydrogel. Issue 43 (29th September 2016) - Skilling, K. J.; Kellam, B.; Ashford, M.; Bradshaw, T. D.; Marlow, M.
Abstract : Development of a self-healing nucleoside hydrogel using N 4-octanoyl-2′-deoxycytidine (0.5% w/v) for drug delivery. Abstract : Low molecular weight gelator hydrogels provide a viable alternative to traditional polymer based drug delivery platforms, owing to their tunable stability and in most cases inherent biocompatibility. Here we report the first self-healing nucleoside hydrogel using N 4-octanoyl-2′-deoxycytidine (0.5% w/v) for drug delivery. The hydrogel's cross-linked nanofibrillar structure, was characterised using oscillatory rheology and confirmed using SEM and TEM imaging. The potential of this gel for drug delivery was explored in vitro using fluorescently labelled tracers. Cell viability assays were conducted using pancreatic cell lines which tolerated the gels well; whilst no adverse effects on the viability or proliferation of cells were observed for fibroblast cell lines.